Renewable energy systems : design and analysis with induction generators - Simoes, M.Godoy, ....-; Farret, Felix A., ....- (Boca Raton : CRC, 2004)
Renewable Energy Systems: Design and Analysis with Induction Generators focuses on renewable energy applications with emphasis on the modeling, driving, and use of induction generators for power generation. It covers all topics related to design, operation, and overall analysis of such systems as well as everything from the very basic topics on induction generators to the latest technologies for association, controls, automation, and power electronics. Each chapter introduces a feature problem related to the technology discussed in that chapter and then solves the problem and proposes additional exercises. The use of MATLAB and Simulink is integrated throughout the book
Keywords: Asynchrone machines; Duurzame energie; Elektrische energie; Windturbines